HAK KONSTITUSIONAL ATAS LINGKUNGAN HIDUP YANG BAIK DAN SEHAT SEBAGAI HAK KEWARGANEGARAAN: SCOPING REVIEW LITERATUR CIVIC LAW DI INDONESIA - Rahmaddani, Imam (Gapenas Publisher, 2025)
The climate crisis, pollution, and ecological degradation have strengthened the urgency of the right to a good and healthy environment as an integral part of human rights and citizens’ constitutional rights. Indonesia is relatively progressive, as it has incorporated the right to a good and healthy environment into Article 28H(1) of the 1945 Constitution and elaborated it in Law No. 32 of 2009 on Environmental Protection and Management. Normatively, this right is framed as both a human right and a constitutional right of citizens. However, there is a persistent gap between normative guarantees and empirical implementation, and only a limited number of studies explicitly interpret the right to a healthy environment as a citizenship right from a civic law perspective. This article aims: (1) to map the development of literature on the right to a good and healthy environment as a constitutional right of citizens in Indonesia; (2) to identify theoretical and methodological approaches used; (3) to reveal theoretical and empirical gaps in existing studies; and (4) to propose a conceptual framework of environmental rights as citizenship rights that integrates environmental constitutionalism, environmental citizenship, and environmental justice. The research applies a qualitative scoping review guided by Arksey and O’Malley’s framework, refined by Levac et al., and reported with reference to PRISMA-ScR. The findings show that Indonesian scholarship is dominated by normative legal research focusing on constitutional texts and legislation, while the dimensions of citizenship, public participation, and environmental justice remain underexplored. At the same time, ecological citizenship discourse has developed rapidly in citizenship education studies, but it is not yet firmly connected to the constitutional foundations of environmental rights. The article proposes a civic law framework that conceptualises the right to a good and healthy environment as a living civic right and identifies a set of future research agendas to strengthen the connections between law, citizenship, and environmental justice in Indonesia